2002
DOI: 10.1002/jsfa.1101
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the clotting properties of sheep milk

Abstract: A Formagraph was used to test the effects of some of the exogenous factors that can affect the processing properties of milk (pH, soluble calcium, rennet concentration, coagulation temperature), and two of the endogenous factors (protein and fat concentration), on the comparative clotting properties of sheep and cows' milk, namely renneting time (r), rate of ®rming (k20) and curd consistency (A30). A lower pH decreased r and k20 and increased A30 in both sheep and cows' milk. The addition of calcium chloride d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
1
13

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 35 publications
7
56
1
13
Order By: Relevance
“…On the other hand, Jelínek et al (1990) reported that from 90th day of lactation the CT gradually shortened till the end of lactation. In our opinion, elongation of CT in our study was mainly influenced by the gradual increase of the contents of TP, casein Bencini (2002) reported that pH of sheep milk is a factor of paramount importance of the rennet coagulation time, but in our study no significant correlation between these parameters was found.…”
Section: Resultscontrasting
confidence: 64%
“…On the other hand, Jelínek et al (1990) reported that from 90th day of lactation the CT gradually shortened till the end of lactation. In our opinion, elongation of CT in our study was mainly influenced by the gradual increase of the contents of TP, casein Bencini (2002) reported that pH of sheep milk is a factor of paramount importance of the rennet coagulation time, but in our study no significant correlation between these parameters was found.…”
Section: Resultscontrasting
confidence: 64%
“…There were no significant differences among the groups with regard to SCC, TBC, or milk clotting ability (r, k 20 , and a 30 ) (Table 3). However, it is worth noting that in all diets, milk urea levels were within normal limits for dairy ewes (Cannas et al 1998), and the milk clotting parameters were close to those recorded for sheep milk (Bencini 2002).…”
Section: Milk Yield and Propertiessupporting
confidence: 64%
“…The content of milk components (mainly fat and protein) and also other factors such as casein micelle diameter and mineral equilibrium, which also change during lactation, can affect curd firmness (Remeuf et al, 1991;Pellegrini et al, 1997). Bencini (2002) found that increasing the protein content (4.9%-6.84%, pH 6.71) of ewe milk decreased its rennet clotting time (RCT) and increased its curd consistency, but the same author reported that the relationship between the concentration of milk protein and curd firmness is curvilinear and curd does not increase when the milk protein exceeds ≈ 6.3%. The same observation was made for a high fat content of milk -curd consistency increases when the fat concentration in milk is less than 6.85%.…”
Section: Discussionmentioning
confidence: 99%